2018
DOI: 10.1016/j.freeradbiomed.2018.10.422
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of oxidative stress-induced lesions in skeletal muscle in a mouse model of obesity-independent hyperlipidaemia and atherosclerosis through the inhibition of Nox2 activity

Abstract: Attenuation of oxidative stress-induced lesions in skeletal muscle in a mouse model of obesity-independent hyperlipidaemia and atherosclerosis through the inhibition of Nox2 activity, Free Radical Biology and Medicine,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 90 publications
2
22
0
Order By: Relevance
“…One study has confirmed that TMZ enhanced mitochondrial respiratory function and promoted mitochondrial biosynthesis in cardiomyocytes (Shi, Shangguan, Zhang, Li, & Li, ). A recent study also showed that TMZ attenuated SMV‐associated skeletal muscle injury in ApoE −/− mice (Song et al, ), which is an established model of atherosclerosis that develops hyperlipidaemia and atherosclerotic (Sfyri et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…One study has confirmed that TMZ enhanced mitochondrial respiratory function and promoted mitochondrial biosynthesis in cardiomyocytes (Shi, Shangguan, Zhang, Li, & Li, ). A recent study also showed that TMZ attenuated SMV‐associated skeletal muscle injury in ApoE −/− mice (Song et al, ), which is an established model of atherosclerosis that develops hyperlipidaemia and atherosclerotic (Sfyri et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…Recent evidence indicates a direct link between the production of diet‐induced reactive oxygen species (ROS) and levels of oxidative protein modifications such as 4‐hydroxynonenal (4‐HNE) and 3‐nitrotyrosine (3NT) adducts that are involved in the development of metabolic disorders . Loss of CD36 is known to attenuate ROS production, alleviating oxidative stress .…”
Section: Resultsmentioning
confidence: 99%
“…Gastrocnemius and liver lipid profiling was performed by using a combination of thin‐layer chromatography and gas chromatography as previously described . Tissue was pulverized by manual mortar and pestle grinding in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations